Ototoxicity and cochlear sparing in children with medulloblastoma: Proton vs. photon radiotherapy. Issue 1 (July 2018) - Paulino, Arnold C.; Mahajan, Anita; Ye, Rong; Grosshans, David R.; Fatih Okcu, M.; Su, Jack; McAleer, Mary Frances; McGovern, Susan; Mangona, Victor A.; Chintagumpala, Murali
Abstract: Purpose: To compare ototoxicity rates between medulloblastoma patients treated with protons vs. photons. Materials and methods: The study included 84 children diagnosed with medulloblastoma treated with either passively scattered protons ( n = 38) or photons ( n = 46). Patients underwent maximal safe resection followed by craniospinal irradiation, posterior fossa and/or tumor bed boost and chemotherapy according to one of 3 multi-institutional trials. Median audiogram follow-up was 56 months for protons and 66 months for photons. Results: Mean cochlear dose (Dmc ) was lower in patients treated with protons for both standard ( p < 0.0001) and high-risk disease ( p < 0.001). Grade 3 and 4 ototoxicity was seen in 7 of 75 (9.3%) and 9 of 91 (9.9%) ears (Brock, p = 0.91), 13 of 75 (17.3%) and 19 of 91 (20.9%) ears (POG, p = 0.56), and 15 of 75 (20.0%) and 21 of 91 (23.1%) ears (SIOP Boston, p = 0.63) with protons and photons respectively. Conclusions: While cochlear doses were lower in the proton group, patients treated with either protons or photons had similar Grade 3 and 4 ototoxicity rates.